PERAN KINERJA LINGKUNGAN SEBAGAI VARIABEL MODERASI DALAM HUBUNGAN AKUNTANSI HIJAU DAN KINERJA KEUANGAN - Devia Septyani; Maya Matofani (CV. Lafadz Jaya, 2026)
This study aims to analyze the effect of green accounting on financial performance and the role of environmental performance as a moderating variable in energy and mining sector companies listed on the LQ45 index. The study used a quantitative approach with secondary data in the form of company annual reports for the 2022–2024 period. Green accounting was measured using the KSCI index, financial performance was proxied by Return on Assets (ROA), and environmental performance was measured using the PROPER rating. Data analysis was performed using linear regression using SPSS 24, accompanied by normality tests, t-tests, and coefficient of determination tests. The results showed that green accounting had a positive and significant effect on financial performance. Environmental performance directly negatively affected financial performance in the short term, indicating environmental compliance costs. However, when environmental performance acted as a moderating variable, the relationship between green accounting and financial performance became stronger, as reflected in an increase in the R-square value of 76.3%. This finding supports stakeholder theory and legitimacy, suggesting that sustainable practices accompanied by good environmental performance can improve the effectiveness of a company's financial performance.